Bibliometric Analysis on Regenerative Design and Sustainability - Ovalı, Pınar Kısa; Gider, Güzide (Fırat University, 2025)
The building approach of the 21st century is developing within the framework of sustainability. Regenerative design, one of the sub-approaches of sustainable architectural understanding, aims not only to reduce environmental impacts but also to create a positive effect on the ecosystem. In this study, scientific publications in the fields of regenerative design and sustainability were evaluated using bibliometric analysis. A total of 363 articles published between 1993 and 2025 in the Web of Science database were analyzed to identify influential authors, universities, leading countries, journals, and keywords. The findings show that the number of publications has increased over time, with the keywords “sustainability” and “design” among the most frequently mentioned. The most relevant authors were Naboni E., Zari M. P., Cole R. J., and Pedersen Zari M., while the journal Sustainability held a leading position among journals. The University of Toronto stood out among universities. The majority of scientific studies were conducted in the United States and the United Kingdom, and no articles from Turkey were found. This situation can be explained by the fact that regenerative design has only recently begun to be studied in our country, and that the majority of the studies consist of theses.

21.Yüzyılın yapılaşma anlayışı sürdürülebilirlik çerçevesinde gelişmektedir. Sürdürülebilir mimari anlayışının alt yaklaşımlarından biri olan rejeneratif tasarım, yalnızca çevresel etkileri azaltmakla kalmayıp aynı zamanda ekosistemde pozitif etki yaratmayı amaçlamaktadır. Çalışmada, rejeneratif tasarım ve sürdürülebilirlik alanlarında yapılan bilimsel yayınlar bibliyometrik analiz yöntemiyle değerlendirilmiştir. Web of Science veri tabanında 1993-2025 yılları arasında yayımlanan 363 adet makale analiz edilerek etkili yazarlar, üniversiteler, önde gelen ülkeler, dergiler ve anahtar kelimeler belirlenmiştir. Bulgular, yapılan yayınların zamanla arttığını, sustainability ve design anahtar kelimelerinin en sık bahsedilenler içinde olduğunu, en ilgili yazarlar olarak Naboni E., Zari M. P., Cole R. J. ve Pedersen Zari M.’ nin öne çıktığını, dergiler içinde Sustainability dergisinin lider konumda olduğunu, üniversiteler içinde ise Toronto Üniversitesi’nin öne çıktığını göstermektedir. En fazla bilimsel çalışma Amerika Birleşik Devletleri ve İngiltere’de yürütülmüş olup, Türkiye’den herhangi bir makaleye rastlanmamıştır. Bu durum, rejeneratif tasarımın ülkemizde yeni yeni incelenmeye başlanması ve çalışmaların büyük çoğunluğunu tezlerin oluşturmasıyla açıklanabilir.
Rejeneratif Tasarım ve Sürdürülebilirlik Üzerine Bibliyometrik Analiz
Keywords: Architectural Design; Mimari Tasarım; Sustainable Architecture; Sürdürülebilir Mimari